THE PRESERVATION OF THE COMPANY AS A FUNDAMENTAL PRINCIPLE: THE MAINTENANCE OF BUSINESS AND ECONOMIC ACTIVITY, ITS SOCIAL FUNCTION, AND THE COLLECTIVE INTEREST - Maromba, Alexandre Machado; Lemos Junior, Eloy Pereira (Seven Editora, 2025)
This paper analyzes the preservation of the enterprise as a fundamental principle implicit in the 1988 Federal Constitution, recognizing the enterprise as an essential vector for the realization of fundamental rights and the enforcement of social justice in the economic order. The article seeks to demonstrate that the enterprise, conceived not only as an economic entity but also as a legal and social institution, plays a structuring role in contemporary society, constituting an instrument for realizing the constitutional values of free enterprise, the valorization of human labor, and the dignity of the human person. To this end, a deductive methodology is employed, with bibliographical research and doctrinal analysis, addressing the interconnection between economics, law, and constitutional foundations. Based on this, the article argues that the principle of preservation of the enterprise should be understood beyond Law n. 11.101/2005, encompassing all phases of business life, as a way to ensure the continuity of productive activity and the protection of collective interests. It is argued that this principle, although not expressly stated, has an implicit constitutional nature, radiating from the regulatory system and integrating the core of the Brazilian economic Constitution, as a guarantee of social stability, job creation, and the promotion of sustainable development.DOI: https://doi.org/10.56238/sevened2025.036-066